Comparative Study of Mosque and Church Construction Management in Majority-Minority Religious Communities: Cases from Manado and Gorontalo - Jan, Radlyah Hasan; Hasan, Youlanda; Figueiredo, António José Pereira; Kirin, Arwansyah bin (Kawanua International Journal of Multicultural Studies, 2024)
Religious diversity in Indonesia presents unique challenges in managing houses of worship construction, particularly in areas where religious groups constitute a minority. This study investigates the management of mosque construction in Manado, a predominantly Christian city, and church construction in Gorontalo, a predominantly Muslim city. Using a qualitative approach, data were collected through interviews with key informants including mosque and church committee leaders, religious leaders, and local government officials, as well as through direct observation and documentation analysis. The findings revealed five critical elements in worship house construction management: planning processes, funding sources, organizational structure, implementation strategies, and evaluation mechanisms. The study found that while both cities maintain religious tolerance, management approaches differ significantly between majority and minority contexts. In Manado, mosque construction faced challenges primarily in financial management and internal organizational conflicts, while in Gorontalo, church construction encountered regulatory hurdles despite facing fewer social obstacles. These findings have important implications for religious policy development and interfaith relations in pluralistic societies, suggesting the need for more structured management approaches in worship house construction that consider both technical and socio-religious factors.